Water-soluble phthalocyanine photosensitizers for photodynamic therapy - Omeroglu, Ipek; Durmuş, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2023)
Photodynamic therapy (PDT) is based on a photochemical reaction that is started when a photosensitizing process is activated by the light and results in the death of tumor cells. Solubility is crucial in PDT applications to investigate the physical and chemical characteristics of phthalocyanines, but, unfortunately, most phthalocyanines show limited solubility especially in water. To increase the solubility of phthalocyanines in polar solvents and water, ionic groups such as-SO3-,-NR3+,-COO-, and nonionic groups such as polyoxy chains are frequently added to the peripheral or nonperipheral positions of the phthalocyanine framework. Since water-solubility and NIR-absorbing properties are essential for efficient PDT activation, studies have been focused on the synthesis of these types of phthalocyanine derivatives. This review focuses on the photophysical, photochemical, and some in vitro or in vivo studies of the recently published ionic and nonionic phthalocyanine-mediated photosensitizers carried out in the last five years. This review will have positive contributions to future studies on phthalocyanine chemistry and their PDT applications as well as photochemistry.
Keywords: Phthalocyanine; water-soluble; photodynamic therapy; ionic or nonionic; photosensitizer; singlet oxygen